Matter in equilibrium - Berry, R. Stephen (Oxford University Press, 2002)
Originally Part II of Physical Chemistry, Second Edition, and now published as its own volume, Matter in Equilibrium: Statistical Mechanics and Thermodynamics simultaneously develops the statistical molecular theory and the classical thermodynamic theory of the bulk properties of matter in a mutually reinforcing fashion. Despite presenting both a microscopic and macroscopic approach, this sophisticated text offers a rigorous treatment of classical thermodynamics and allows professors to separate the two theories if desired. Packed with tables, graphs, and figures, it describes the equilibrium properties of bulk matter and develops the tools needed to study gases, solids, liquids, phase transformations, solutions of nonelectrolytes, and solutions of electrolytes. The book makes extensive use of computer simulations of molecular behavior and, where appropriate, uses experimental data to illustrate concepts and principles. Ideal for advanced undergraduate and beginning graduate level courses, Matter in Equilibrium broadens and challenges student perspectives while offering valuable information to researchers